2014
DOI: 10.1177/1077546314544513
|View full text |Cite
|
Sign up to set email alerts
|

Size dependent effect on the buckling and vibration analysis of double-bonded nanocomposite piezoelectric plate reinforced by boron nitride nanotube based on modified couple stress theory

Abstract: In this article, the buckling and vibration analysis of a double-bonded nanocomposite piezoelectric plate reinforced by a boron nitride nanotube based on the Eshelby-Mori-Tanaka approach is developed using modified couple stress theory under electro-thermo-mechanical loadings surrounded by an elastic foundation. Using Hamilton's principle, the governing equations of motion are obtained by applying a modified couple stress theory and the Eshelby-Mori-Tanaka approach for piezoelectric material and Kirchhoff plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…In addition, λ and μ denote the two Lame constants, ℓ is the material length scale parameter, and δij is the Kronecker delta. Moreover, components of the displacement and rotation vectors are defined by u and θ, respectively, where the rotation vector is related to the displacement vector as 31,32 …”
Section: Preliminariesmentioning
confidence: 99%
“…In addition, λ and μ denote the two Lame constants, ℓ is the material length scale parameter, and δij is the Kronecker delta. Moreover, components of the displacement and rotation vectors are defined by u and θ, respectively, where the rotation vector is related to the displacement vector as 31,32 …”
Section: Preliminariesmentioning
confidence: 99%
“…The free vibration analysis of SWCNT using modified strain gradient and the thin shell theories is presented by Zeighampour and Tadi Beni [32]. They demonstrated that the natural frequencies of SWCNTs obtained by MSGT are larger than that of in couple stress model and CT. Mohammadimehr et al [33] considered the size dependent effect on the buckling and vibration analysis of double-bonded nanocomposite piezoelectric plate reinforced by boron nitride nanotube using MCST. They investigated the effects of material length scale parameter, elastic foundation coefficients, aspect ratio (a/b), length-to-thickness ratio (a/h), transverse and longitudinal wave numbers on the dimensionless natural frequency.…”
Section: -Intruductionmentioning
confidence: 99%
“…Substituting equations (14), (19) and (21) into equation (20), the governing equation of motion for nonlocal SLGS using energy method is obtained as follows…”
Section: Basic Formulations Of the Problemmentioning
confidence: 99%